2000
DOI: 10.1089/089771500415418
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autoregulation of Cerebral Blood Flow in an Experimental Model of Traumatic Brain Injury

Abstract: In order to study the pathophysiology and the intracranial hemodynamics of traumatic brain injury, we have developed a modified closed-head injury model of impact-acceleration that expresses several features of severe head injury in humans, including acute and long-lasting intracranial hypertension, diffuse axonal injury, neuronal necrosis, bleeding, and edema. In view of the clinical relevance of impaired autoregulation of cerebral blood flow after traumatic brain injury, and aiming at further characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 43 publications
4
31
2
Order By: Relevance
“…Our results are partially in contrast to recent studies reporting a significant increase in focal tissue injury or sustained neurologic deficit related to the superimposed HH in more severe models of weight-drop brain injury in rats (37). Interestingly, using a mild FP brain injury model, Matushita et al (9) reported an exacerbation of tissue damage with the superimposed HH (MABP 50-60 mm Hg for 30 mins).…”
Section: Histopathologic Damagecontrasting
confidence: 99%
“…Our results are partially in contrast to recent studies reporting a significant increase in focal tissue injury or sustained neurologic deficit related to the superimposed HH in more severe models of weight-drop brain injury in rats (37). Interestingly, using a mild FP brain injury model, Matushita et al (9) reported an exacerbation of tissue damage with the superimposed HH (MABP 50-60 mm Hg for 30 mins).…”
Section: Histopathologic Damagecontrasting
confidence: 99%
“…This still is considered sufficient, at least in TBI patients according to the Brain Trauma Foundation guidelines. After TBI a dysfunction in cerebral autoregulation might occur [32] and also the microcirculation seems to be dysregulated leading to distended arterioles (Glushakova et al 2014 epub) and thus more intracerebral blood volume. As consequence ICP can be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…The caliber changes of the autoregulatory vessels are mediated by myogenic, metabolic, or neurogenic mechanisms (Brownlee & Langille, 1991;Bryan et al, 1995;Busto et al, 1997). The smaller arterioles dilate proportionately more than larger arterioles at a mean arterial blood pressure below physiological levels (Ellis et al, 1979;Engelborghs et al, 2000). However, larger arterioles tend to be more responsive than smaller arterioles at normal and increased levels of arterial pressure (Engelborghs et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The smaller arterioles dilate proportionately more than larger arterioles at a mean arterial blood pressure below physiological levels (Ellis et al, 1979;Engelborghs et al, 2000). However, larger arterioles tend to be more responsive than smaller arterioles at normal and increased levels of arterial pressure (Engelborghs et al, 2000). The other findings associated with CBF reduction at early time points after TBI is the increased cytokine expression and production, however the role of their activity changes is not clear yet (Ahn et al, 2004).…”
Section: Resultsmentioning
confidence: 99%